PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN BERHITUNG DI TAMAN KANAK-KANAK BINA BARU PROVINSI BENGKULU - Anisah Hayanun; Indra Yeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low learning interest and low engagement of children in the learning process have resulted in their low numeracy skills. This study aims to describe the application of audiovisual media as an effort to improve students' learning interest at Taman Kanak-Kanak Bina Baru. The method employed is Classroom Action Research (CAR) based on Kurt Lewin’s model, conducted in two cycles; each cycle consists of the stages of planning, action, observation, and reflection. The research subjects are children of Group B at Taman Kanak-Kanak Bina Baru, Bengkulu Province, for the academic year 2025/2026, comprising 15 children in total: 9 boys and 6 girls. Observation, assessment, and documentation are the data collection methods used by the researcher. The research results show an improvement in students' learning interest after the implementation of audiovisual media. The percentage of children achieving "very well-developed" competence in numeracy rose from the initial 13.3% (only 5 students) to 60.0% (9 students) after audiovisual media was applied in numeracy learning during Cycle II.